2011
DOI: 10.1037/a0022531
|View full text |Cite
|
Sign up to set email alerts
|

Seeing a phrase “time and again” matters: The role of phrasal frequency in the processing of multiword sequences.

Abstract: Are speakers sensitive to the frequency with which phrases occur in language? The authors report an eye-tracking study that investigates this by examining the processing of multiword sequences that differ in phrasal frequency by native and proficient nonnative English speakers. Participants read sentences containing 3-word binomial phrases (bride and groom) and their reversed forms (groom and bride), which are identical in syntax and meaning but that differ in phrasal frequency. Mixed-effects modeling revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
283
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(331 citation statements)
references
References 45 publications
41
283
6
1
Order By: Relevance
“…This finding is in line with previous studies in the field of language production that have examined the impact of phrase frequency on measures of phonological reduction [26], and agrees with findings from the field of language comprehension [17,[20][21][22][23][24][25]. For example, as discussed in the Introduction, Arnon and Snider [17] found that recognition times of multi-word phrases were sensitive to the frequency with which the phrases appeared in the language.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with previous studies in the field of language production that have examined the impact of phrase frequency on measures of phonological reduction [26], and agrees with findings from the field of language comprehension [17,[20][21][22][23][24][25]. For example, as discussed in the Introduction, Arnon and Snider [17] found that recognition times of multi-word phrases were sensitive to the frequency with which the phrases appeared in the language.…”
Section: Discussionsupporting
confidence: 90%
“…This view assumes that the language system is sensitive to the distribution of linguistic information at grain-sizes beyond individual words. Within such a system, the observed phrase frequency effect might reflect transitional probabilities between individually stored words [46][47][48], the connection weights between low-level input and higher level output representations [5][6][7], or the retrieval of multi-word chunks from memory [20,26]. A pertinent question for future research would be to distinguish between these three possible explanations of the phrase frequency effects observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Only the overall familiarity of the specific construction should affect processing. The fact that both children and adults are sensitive to the overall frequency of multi-word combinations [72][73][74][75] supports this prediction 2 , but further studies are needed to determine how closely the representations of frequent 'flat' word sequences resemble that of possibly hierarchical constructions and idioms.…”
Section: (D) Psychologymentioning
confidence: 99%
“…8, No. 8;2015 Since in this study, the reaction time for written formulaic sequences is significantly shorter than that of idioms, we did a post hoc analysis on their frequency differences. We compared the frequency lists of both types, and found that the average frequency of written formulaic sequences (average frequency in BNC= 4667) are significantly higher than that of the idioms (average frequency in BNC=296) (p=.000).…”
Section: Iii)mentioning
confidence: 95%
“…A recent eye-tracking study by Siyanova-Chanturia, Conklin and Van Heuven (2011) investigated processing of formulaic sequences with different phrasal frequency. It has been revealed that first, frequent formulaic sequences are processed faster than less frequent ones; second, regardless of frequency, native speakers processed the entrenched binomials significantly faster than reversed forms.…”
Section: Literature Reviewmentioning
confidence: 99%